(untitled) (Fiep Bulletin - online, 2015)
Trying to increase the force in search of the best rowing performance it is common to observe in the athletes parafunctional movements, defined as not related muscular contractions to the motor gesture. This habit, generally buccal, would have to be diagnosed/controlled the earlier as possible therefore it can cause damages to the masticatory system and temporomandibular disorders. In these muscular movements occur spasms and, thus, areas of more raised temperatures. The present study had as objective to evaluate the activity of the muscle masseter through Termography, and to relate possible evidences of temporomandibular dysfunction with temperature. Nine rowers had participated. For temporomandibular dysfunction identification was used a questionnaire. The collection was carried through in a rowing simulator and for the thermal register a Termovisor with sensitivity of 0,1ºC. was used. One had carried through 11 measurements for each citizen. There was presence of signals and/or symptoms of temporomandibular dysfunction in three citizens, being that only one of them presented the triad of the symptomatology. For the only citizen that presented the triad the temperature varied 1,5ºC, greater and more expressive in relation to the other citizens. As method, the Termography revealed to be efficient in the evaluation of the activity of the muscle masseter becoming possible an evaluation for a not invasive method for the diagnosis of musculoskeletals dysfunctions. The biggest variation of temperature presented for the only citizen with temporomandibular dysfunction triad seems to show evidences that this method can be used as an alternative of evaluation and/or diagnosis.